Time of the day and season distribution among stroke code subtypes: differences between ischemic stroke, intracranial hemorrhage, and stroke mimic - Menéndez Albarracín, Alex; Valls Carbó, Adrián; Rabaneda Lombarte, Neus; Yugueros Baena, Bárbara; Carbonell Gisbert, Jaime; Flores-Pina, Belén; Larrañaga De Bofarull, Maria-Clara; Martínez Sánchez, Marina; Hernández-Pérez, María; Bustamante Rangel, Alejandro; Dorado Bouix, Laura; Gomis Cortina, Meritxell; et al. (Frontiers in Neurology, 2024)
Background: Circadian variations in the timing of onset of stroke symptoms have been described, showing a morning excess of cardiovascular risk. To date, no differences have been found between stroke subtype and time distribution through the day. The present study aim to compare the seasonal and circadian rhythm of symptoms onset of ischemic, hemorrhagic and stroke mimic patients.Methods: Prospective, hospital-based study on a cohort of stroke alert patients from 2018 to 2021. Stroke subtype was classified as ischemic stroke, intracerebral hemorrhage (ICH), transient ischemic attack (TIA) and stroke mimic. Clinical variables were recorded and each patient was assigned to a 4-hour interval slot of the day according to the time of onset of symptoms; unwitnessed stroke patients were analyzed separately. Seasonal changes in stroke distribution were analyzed by 3 month intervals.Results: A total of 2348 patients were included in this analysis (ischemic 67%, ICH 13%, mimic 16% and TIA 3%). Most of the patients were distributed in the 08-12 and 12-16 hour period regardless of stroke subtype. Significant differences were found between time distribution depending on stroke subtype, showing predominance of ICH in the 04-08 hours period (dawn), most of which were of hypertensive cause, TIA in the 12-16 hours period (afternoon) and stroke mimic in the 20-00 hours period (evening). Ischemic stroke was evenly distributed through the different periods of the day. There were no differences in the seasonal pattern between different stroke subtypes, winter being the one that accumulated most cases.The present study showed different circadian patterns of stroke subtypes, with a predominance of ICH in dawn and stroke mimic in afternoon. Stroke circadian rhythm resembles previous studies, with a higher incidence in the morning and a second peak in the afternoon.